Strategies for promoting achievement motivation among the underachieving gifted students (2013)
The underachievement of gifted children is an area of concern for many parents, teachers and educators generally. Although the study of student underachievement has a long educational history, it is more productive to consider what motivates gifted students to do well. Students tend to be motivated when they find their efforts supported by those around them. in this paper, effort has been made to state the concept of underachievement, causes of underachievement among the gifted learners and strategies for promoting achievement motivation among the underachieving gifted students. The factors that motivate a gifted underachiever to accomplish a given task were explained as well. as some motivation strategies like: utility motivation strategies, intrinsic motivation strategies, motivation strategies to recognize growth, motivation strategies to encourage mastery attribution, motivation strategies to enhance environmental perceptions, motivation strategies to promote study skills and motivation strategies for self-regulation. in conclusion. the way and manner parents and teachers can intervene and reverse underachievement of gifted learners both individually and collectively were ,extensively examined. It was recommended that parents should be role models and must provide their children with opportunities to develop their own interests and areas of giftedness. Teachers in their own case, must know their students, incorporate the students’ gifts and must be supportive, kind and open.